Recent investigation of the medicinal plants’ effectiveness in the natural management of urinary and gallstones: a review - Youssef Miyah; Mohammed Benjelloun; Hajar El Omari; Karima El-Mouhdi; Mohammed El Feniche (Phytomedicine Plus)
Background: The search for natural management techniques using medicinal plants is driven by the inescapable health problems of kidneys and gallstones, which can lead to serious complications and acute pain. These issues are often linked to an unbalanced diet, inadequate hydration, family history, and high doses of certain drugs. Conventional treatments for urinary and gallstones have limited efficacy and do not always guarantee a complete cure, which increases the risk of complications, particularly recurrence. Purpose: This review paper thoroughly examines medicinal plants' potential to treat and prevent gallstones and urinary tract stones and envision a future when natural remedies integrate with conventional medical practices. Study design: This study looks at kidney and biliary diseases, particularly stones, explores conventional treatments (drugs, lithotripsy, and surgery), and highlights medicinal plants used as natural remedies. Several medicinal traditions are examined for their historical use and preparations. By analyzing phytochemistry and prevention mechanisms, research focuses on medicinal plants' active principles and modes of action and their therapeutic and preventive effect against stones. It also examines how these plants can reduce the risk of stone formation, provide an alternative to conventional treatments, and reduce the need for surgery. The study also discusses the importance of a suitable diet and lifestyle to prevent stones. The advantages and disadvantages of herbal remedies are also explored in addition to recommendations for future clinical research into their efficacy. Conclusion: Medicinal plants could be a viable alternative to traditional treatments, especially for biliary and kidney stones. Although this study shows promise in both prevention and treatment, more clinical trials are necessary to fully investigate the efficacy and safety of these natural remedies to confirm their value in a broader medical setting.